Because she's worth it: the natural blonde from Grace Kelly to Nicole Kidman. Issue 1 (2nd January 2016) - Cook, Pam
Abstract : This article investigates the phenomenon of the 'natural blonde' as an ideal of feminine beauty, looking at notions of blond glamour in the 1950s and their deconstruction in recent periods. The article explores the fabricated nature of natural blondness and its relationship to changes in the beauty industry, stardom and celebrity culture since the late 1940s. The role of the beauty industry in fashioning star identities is analysed in relation to Grace Kelly, whose smooth, wavy, fair hair was a crucial element in defining her style as the ultimate cool blonde, an icon of understated elegance and impeccable grooming. Her 'natural blonde' look was crafted to produce an aspirational image of white femininity with specific class attributes, an ideal that was challenged in her film roles. Social change contributed to the decline of this ideal, as 'natural' beauty increasingly became something that could be acquired rather than an innate quality, and 'ironic blondness' gathered momentum. Nicole Kidman's trajectory from flame-haired tomboy to epitome of manufactured blond star glamour, along with her impersonation of Grace Kelly in the 2014 film Grace of Monaco, is used to illuminate these cultural shifts.